Faktor Pemilihan Metode Kontrasepsi Jangka Panjang pada Akseptor KB: Studi di Wilayah Kerja Puskesmas Sukabumi Kota Probolinggo - Karinda Permata Sari; Windhu Purnomo (Viva Medika, 2023)
The program to increase the use of LARC is the main focus of the family planning program in preventing the adverse effects of the population explosion by adjusting the time, spacing and number of pregnancies for couples of childbearing age and reducing the Maternal Mortality Rate (MMR). The coverage of KB LARC acceptors in the Working Area of ​​the Sukabumi Health Center is only 15.5% or below the national target (25.9%). This study aims to analyze factors related to the selection of MKJP for family planning acceptors in the working area of ​​the Sukabumi Health Center, Probolinggo City in 2023 with a quantitative case-control design study with a retrospective approach then use simple random sampling from the study population of 1,980 family planning acceptors and 88 samples comprising 44 LARC FP acceptors and 44 Non-LARC FP acceptors. Primary data was obtained by distributing questionnaires and then univariate and bivariate analysis was performed using the chi-square test. The results of the study mentioned age (p=0.001), number of children (p=0.002), employment status (p=0.018), knowledge (p=0.003), attitude (p=0.033), spousal support (p=0.030) and role health workers (p=0.000) had a relationship. In contrast, an education level (p=0.089) had no association with the selection of LARC acceptors in the Working Area of ​​the Sukabumi Health Center.